AI-Powered Negotiations: Opportunities, Challenges, and the Future of Business Strategy - Li, Hanjie (Transactions on Economics, Business and Management Research, 2024)
Business negotiations are integral to various aspects of enterprise operations, from recruitment and resource allocation to procurement and international business collaborations. Despite their critical importance, negotiations often remain cumbersome, complex, and time-consuming, with outcomes heavily influenced by the negotiator's skills and external factors, frequently failing to maximize benefits or achieve desired goals. The rapid advancement of artificial intelligence (AI) technologies, particularly large language models (LLMs) like ChatGPT, has seen AI increasingly integrated into daily tasks such as drafting emails and querying legal clauses. This paper investigates the potential of AI and negotiation agents to enhance efficiency and optimize outcomes in business negotiations. Utilizing case studies, the research explores how AI can assist or even replace human negotiators by automating data collection, analyzing historical negotiation patterns, predicting outcomes, and suggesting optimal strategies. The findings indicate that AI negotiation agents can surpass human performance in certain negotiation scenarios, providing consistent, data-driven insights and adapting strategies in real time based on counterpart responses. However, the research also highlights the limitations of AI in understanding human emotions, cultural nuances, and the ethical implications of AI decision-making. The conclusion emphasizes the promising role of AI in revolutionizing business negotiations while underscoring the necessity for human oversight to address emotional and ethical complexities. This study provides a foundation for further exploration into the integration of AI in negotiation processes, aiming to enhance both efficiency and effectiveness in achieving business objectives.